2013
DOI: 10.1108/ijsms-14-02-2013-b004
|View full text |Cite
|
Sign up to set email alerts
|

Increasing sponsorship effectiveness through brand experience

Abstract: This research investigates whether creating a brand experience during a sponsored event can add to the success of that sponsorship. It is posited that a direct brand experience might harvest its own intrinsic benefits by intensifying consumers' direct contact with the sponsoring brand. To examine this proposition we conducted a quasi-experimental field study. During a sponsored marathon event in April 2010 data were collected. One of the main sponsors of the event, a well known financial services company, crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 76 publications
(179 reference statements)
1
30
0
6
Order By: Relevance
“…When consumers are exposed to event marketing initiatives, this results in an experience, and subsequently shapes a judgment in relation to that initiative (Zarantonello & Schmitt, 2013). Many studies have talked about live events as a key opportunity that engages and connects customers to the live event experience (Akaoui, 2007;Fransen, van Rompay, & Muntinga, 2013). Whelan and Wohlfeil (2006) identified event marketing as a catalyst for engaging a customer with the brand that results in a brand experience.…”
Section: Event Marketing and Brand Experiencementioning
confidence: 96%
See 1 more Smart Citation
“…When consumers are exposed to event marketing initiatives, this results in an experience, and subsequently shapes a judgment in relation to that initiative (Zarantonello & Schmitt, 2013). Many studies have talked about live events as a key opportunity that engages and connects customers to the live event experience (Akaoui, 2007;Fransen, van Rompay, & Muntinga, 2013). Whelan and Wohlfeil (2006) identified event marketing as a catalyst for engaging a customer with the brand that results in a brand experience.…”
Section: Event Marketing and Brand Experiencementioning
confidence: 96%
“…Brand attitudes deal with the general evaluative judgments in relation to a brand, whereas brand experiences are specified as behavioural and internal responses that are non-evaluative. Shamim and Butt (2013) identify that brand experience influences brand attitude positively; Fransen et al (2013) mention that experience increases positive attitudes towards the sponsoring brand; and Zarantonello and Schmitt (2013) found that attitude towards a brand is generated through brand experience. Therefore, it is correct to state that brand experience plays a significant role in developing a consumer's attitude towards any particular brand and it leads to the eighth research proposition of the study.…”
Section: Effects Of Brand Experience On Attitude Formationmentioning
confidence: 97%
“…Uma das possíveis ações no B2B, que trabalha com os atributos emocionais durante as relações da empresa e seus compradores, é o Marketing de Experiência (Brakus, Schmitt, & Zarantonello, 2009;Fransen, Van Rompay, & Muntinga, 2013). A principal característica do Marketing de Experiência é proporcionar experiências onde os indivíduos são estimulados a terem algum tipo de estímulo emocional e assim, convencê-los a uma compra ou a uma boa Brand Equity do produto/empresa organizadora ou promotora de uma determinada experiência (Schmitt, 1999).…”
Section: Introductionunclassified
“…Literature dedicated to measurement of sports sponsorship effectiveness includes investigations where the measurement of the recognisability of sponsors' brands constitutes the main or one of adopted goals, or has played a supporting role in achieving these objectives (see: Ho Keat Leng, 2017;Biscaia et al, 2014;Fransen et al, 2013;Walraven et al, 2014;Aiken et al, 2015). However, examinations of brand recognisability are not the only choice for sponsoring enterprises desiring to assess the effects of their commitment to the sponsorship.…”
Section: Introductionmentioning
confidence: 99%